ON THE SQUARE ROOT OF THE OPERATOR OF STURM-LIOUVILLE FOURTH-ORDER - А.Sh. Shaldanbayev; A.B. Imanbayeva; A.Zh. Beisebayeva; А.А. Shaldanbayeva (Academic Scientific Journal of Computer Science, 2019)
In the present work found the root of the positive operator of the Sturm - Liouville problem of the fourth order, which is invertible composition operator of the Sturm - Liouville problem and its adjoint. The found root does not possess the property of positivity, but is a self-adjoint operator in the essential. One theorem of Putnam of algebraic character is used as a leading idea. It is hoped that the results will find applications in spectral operator theory and theoretical physics.